2013
DOI: 10.1136/emermed-2012-202189
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomised, placebo-controlled trial of oral midazolam plus oral ketamine for sedation of children during laceration repair

Abstract: Objectives To compare the efficacy of oral midazolam alone with a combination of oral midazolam and ketamine in children requiring laceration repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 21 publications
(28 reference statements)
1
31
0
1
Order By: Relevance
“…According to Chow et al (5) and our results, midazolam in combination with ketamine might be a safe alternative. Our results were in accordance with other studies where orally administered midazolam and ketamine were used in other settings like bone marrow aspiration (28) and laceration repair (29). Gubbay et al (30) reported in a letter to the editor that intranasal fentanyl was usually good enough and better than just midazolam.…”
Section: Discussionsupporting
confidence: 92%
“…According to Chow et al (5) and our results, midazolam in combination with ketamine might be a safe alternative. Our results were in accordance with other studies where orally administered midazolam and ketamine were used in other settings like bone marrow aspiration (28) and laceration repair (29). Gubbay et al (30) reported in a letter to the editor that intranasal fentanyl was usually good enough and better than just midazolam.…”
Section: Discussionsupporting
confidence: 92%
“…The level of sedation score>3 was achieved similarly in both the groups at 45minutes.Studies have shown that achieving adequate sedation was more common in children treated with the combination of ketamine and midazolam rather than oral midazolam alone. [6,7,8] Procedural sedation was adequately achieved with fentanyl and midazolam combination in one study. [9] Separation from parents was equally good in both groups however anxiolysis on venepuncture was poor in 28% and 34% cases with midazolam and ketamine respectively.…”
Section: Discussionmentioning
confidence: 99%
“…4 Numerous studies evaluating this combination have been conducted. [4][5][6][7][8][9][10] The authors sought to conduct a structured literature review and narrative synthesis to determine the efficacy and possible adverse effects of this combination when used as a premedication in paediatric patients undergoing elective surgery compared with midazolam alone as a premedication.…”
Section: Introductionmentioning
confidence: 99%